KESADARAN HUKUM MASYARAKAT DALAM MEMANFAATKAN MEDIA SOSIAL ( STUDI TERHADAP GENERASI Z DI KOTA MAGELANG ) - Puspandari, Rr Yunita (Universitas Semarang, 2021)
Social media is a means of delivering information and electronic transactions. Social media users from all over the world, including teenagers who are in the